Female migraineurs show lack of insular thinning with age. Issue 7 (July 2015) - Maleki, Nasim; Barmettler, Gabi; Moulton, Eric A.; Scrivani, Steven; Veggeberg, Rosanna; Spierings, Egilius L.H.; Burstein, Rami; Becerra, Lino; Borsook, David
Abstract : Abstract: Gray matter loss in cortical regions is a normal ageing process for the healthy brain. There have been few studies on the process of ageing of the brain in chronic neurological disorders. In this study, we evaluated changes in the cortical thickness by age in 92 female subjects (46 patients with migraine and 46 healthy controls) using high-field magnetic resonance imaging. The results indicate that in contrast to healthy subjects, migraineurs show a lack of thinning in the insula by age. The functional significance of the lack of thinning is unknown, but it may contribute to the overall cortical hyperexcitability of the migraine brain because the region is tightly involved in a number of major brain networks involved in interoception, salience, nociception, and autonomic function, including the default mode network. Abstract : Adult female migraineurs do not exhibit normal insular thinning with age; this suggests that the region may be important in migraine pathophysiology.